The Barratt Impulsiveness Scale-11 in Community and Incarcerated Samples: Motor and Nonplanning Impulsivity Effects on Criminal Recidivism - Ros, Laura (Criminal justice and behavior, 2020)
Although the Barratt Impulsiveness Scale Version 11 (BIS-11) is one of the most widely used instruments to assess impulsivity, its factor structure remains controversial. Several authors have suggested that cultural factors may have an impact on its factor structure. It is also necessary to study the measurement invariance of the scale in different populations, especially in the case of incarcerated individuals, given their high level of impulsivity. This study had two objectives: (a) to evaluate the factor structure of the BIS-11 and its measurement invariance across community and incarcerated samples and (b) to evaluate the effect of impulsiveness on criminal recidivism. The results revealed a two-factor structure: Motor and Nonplanning Impulsivity. This solution was invariant across groups. In addition, increased Motor Impulsivity was related to higher criminal recidivism through an increase in aggression. These results corroborate the importance of implementing interventions to reduce impulsivity as a means of preventing recidivism.